Building a bicultural bridge - Rodriguez-Keyes, Elizabeth; Piepenbring, Julie (Smith College Studies in Social Work, 2017)
The balancing act of living between two cultures can have a significant impact on the development of adolescent Latinas living in the United States. Many adolescent Latinas, particularly second generation, live with two sets of cultural values that are often in conflict with one another. This case study illustrates the importance of understanding the impact of acculturation on the individual and the family. Issues of identity, biculturalism, and bilingualismspecifically the phenomenon of language switchingare dismantled in this case study to gain deeper insight into the unique experience that second-generation Latinas undergo when negotiating two cultural orientations. These findings are important to consider when working with the Latino population as they represent one of the largest immigrant groups and the most rapidly growing group in the United States.
Keywords: Latinas; adolescent; biculturalism; bilingual psychotherapy; cultural identity; dept.swk; language switching

Cultivating curiosity: integrating hybrid teaching in courses in human behavior in the social environment - Rodriguez-Keyes, Elizabeth; Schneider, Dana A (Journal of Teaching in Social Work, 2013)
This study illustrates an experience of implementing a hybrid model for teaching human behavior in the social environment in an urban university setting. Developing a hybrid model in a BSW program arose out of a desire to reach students in a different way. Designed to promote curiosity and active learning, this particular hybrid model has students engage in weekly online activities between their weekly on-ground classes. This article reviews key pedagogical concerns and presents preliminary findings, including student feedback, instructor observations, and strategies for faculty interested in developing such courses. © 2013 Copyright Taylor and Francis Group, LLC.
Keywords: dept.swk; education; hybrid; online; peer-reviewed; social work; student perceptions; technology

Being known in undergraduate social work education: the role of instructors in fostering student engagement and motivation - Rodriguez-Keyes, Elizabeth; Schneider, Dana A; Keenan, Elizabeth King (Social Work Education, 2013)
Most undergraduate students pursue a social work major because of their desire to help others. Students tend to be more interested in doing than in understanding the research and knowledge of the profession and the complexities of social work practice. Instructors are often faced with the challenge of enhancing student motivation to learn challenging course material. This study explored student perceptions of instructor influences on their motivation and engagement in learning. Through online surveys, students described their experiences of being known and how those experiences affected their participation in practice, research, and human behavior in the social environment courses. Results showed that instructor caring (providing recognition, expressing relational qualities, and responding to students) positively influences student motivation and affective learning by increasing comfort, willingness to ask questions, take risks, and overall participation. Conversely, of those who reported mixed experiences or who felt unknown, most reported a negative impact on their motivation and participation. These findings suggest that social work faculty can influence student motivation and engagement with essential social work curriculum by expressing care and helping students feel known in the classroom. © 2013 Copyright Taylor and Francis Group, LLC.
Keywords: BSW Education; Being Known; Instructor Influence; Motivation; Student Engagement; dept.swk

Seeing Through the Eyes of the Other Using Process Recordings - Schneider, Dana A.; Rodriguez-Keyes, Elizabeth; Keenan, Elizabeth King (Clinical Supervision Activities for Increasing Competence and Self-Awareness, 2014)
This chapter describes a two-step process including videotaping and process-recording activities to facilitate self-awareness and the expression of empathy and acceptance toward other points of view. These activities are designed for beginning student clinicians who are currently completing their coursework and their first clinical internship. The first step of videotaping helps clinicians become more aware of their inner thoughts, feelings, beliefs, and personal values. This first step also helps participating clinicians become more aware of their nonverbal communication with clients, helping them assess how their internal experiences of empathy and acceptance match what is being conveyed nonverbally to their clients. The second step of the activity, process recording, helps clinicians reflect on their ability to use self-awareness to analyze their inner experiences and their outer expressions of empathy and acceptance (both verbal and nonverbal) while still being attuned to their clients' communication.
Keywords: dept.swk; nonverbal communication; process-recording activities; self-awareness; videotaping

Revitalizing the vision in supervision: supporting the supervisor in home-based therapy programs - Rodriguez-Keyes, Elizabeth; Gossart-Walker, Sandy; Rowland, Cecilia (Smith College Studies in Social Work, 2012)
Home-based programs provide a growing number of mental health and case-management services to high-risk children, adolescents, and their families. The clinical service providers who work directly with these children and families have varying degrees of education and practice experience as well as a range of different supervisory needs. Because of the daily challenges service providers face, they require support from competent, available supervisors. The professionals who supervise them often assume that responsibility with limited, if any, training in providing supervision. New and experienced supervisors alike often find themselves in positions for which they are ill prepared, without suitable training or administrative support. This article describes a supervision seminar developed for supervisors who supervise the clinicians who provide home-based services. The seminar provides training, support, consultation, and other forms of assistance to help supervisors adapt their clinical skills for use in their supervisory roles.
Keywords: clinical supervision; clinical supervisor; dept.swk; home-based therapy; supervision seminar